Medicinal Properties of the Golden Oyster Mushroom, Pleurotus citrinopileatus (Agaricomycetes), Grown on Local Agricultural Wastes in Turkey - Inci, Sule; Kirbag, Sevda; Akyuz, Mehmet (Begell House Inc, 2022)
In this study, the antimicrobial, antioxidant, cytotoxicity, and DNA protective effects of Pleurotus citrinopileatus cultured on substrates were investigated. The methanol extract of P. citrinopileatus showed lower activity against Streptococcus mutans (17.0-21.7 mm), Salmonella thypii (12.3-17.7 mm), and Candida tropicalis (16.3-20.3 mm) but was observed to be very active against Trichopyton sp. (14.0-22.3 mm), Bacillus subtilis (17.3-20.3 mm), Pseudomonas aeruginosa (13.0-20.3 mm), Proteus vulgaris (18.3-23.7 mm), Staphylococcus aureus (16.3-23.0 min), and Escherichia coli (16.0-24.0 mm) compared with the control group. P. citrinopileatus demonstrated significant antioxidant potential. The highest total antioxidant assay (2.76 mmol/L) and total oxidant assay (11.98 mu mol/L) values were determined on wheat straw-quinoa stalk (WS-QS; 1: 1) and QS medium, and their effectiveness at removing 2,2-diphenyl-1-picrylhydrazyl radicals was more efficient at groups to which samples of 25 mg (74.72-79.80%) were added. The methanol extracts of P. citrinopileatus grown on WS, QS, and WS-QS (1:1) substrates were found to prevent DNA damage induced by ultraviolet radiation and H2O2 at a concentration of 25 mg/mL. The methanol extract of P. citrinopileatus, which was obtained from WS (2.7%) at a 400-mu g/mL concentration, remarkably decreased the percentage of viability in the A-549 cell line. These results suggest that P. citrinopileatus has potent antimicrobial, antioxidant, and DNA protective as well as cytotoxic effects on the A-549 cell line.
Keywords: Pleurotus citrinopileatus; antimicrobial; antioxidant; cytotoxic; DNA protect effect